THE EFFECTS OF ADHESIVE TYPE AND CONCENTRATION IN THE MANUFACTURING OF FILTER CAKE BRIQUETTES AS AN ALTERNATIVE FUEL - Andes Ismayana dan Moh. Rizal Afriyanto (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTThe objective of this  study was  to determine the effects of adding the type and concentration of an appropriate adhesive material in the manufacturing  of filter cake briquettes.  This study  was conducted by making briquettes using different adhesive materials, i.e.  molasses and tapioca with adhesive levels of  10%, 15%, and 20% for each adhesive material. The results showed that the addition of adhesive   will increase  the density , decrease the rate of combustion , and increase the calory  of briquettes from 1026 calories/gram to 1995 calories/gram. The resulting coal of filter cake briquettes  were good enough by generating coals temperatures between 357 and  496°C. In addition, this filter cake  briquettes produced low ash content and flying substances levels  higher than those of wood charcoal briquettesin  the market.Keywords: filter cake briquette, tapioca, molasses, value of calories, coals temperature